2020
DOI: 10.4266/acc.2019.00731
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of bedside peripherally inserted central catheter placement: a retrospective study at a single institution

Abstract: Outcomes of bedside peripherally inserted central catheter placement: a retrospective study at a single institution Background: Bedside insertion of peripherally inserted central catheters (PICCs) has higher rates of malposition than fluoroscopic-guided PICC placement. This study evaluated the success rate of bedside PICC placement, variations in tip location, and risk factors for malposition. Methods: This retrospective study included patients who underwent bedside PICC placement from January 2013 to Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…In recent studies, success rates defined as proper positioning of the PICC catheter with ultrasound-guided insertion have been reported to be about 81.2% and 94.4% [ 10 , 11 ] in adults and 83.9% [ 12 ] in children. Our success rate of 73.3% was relatively lower than these results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies, success rates defined as proper positioning of the PICC catheter with ultrasound-guided insertion have been reported to be about 81.2% and 94.4% [ 10 , 11 ] in adults and 83.9% [ 12 ] in children. Our success rate of 73.3% was relatively lower than these results.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of malpositioning of the catheter tip is reported to be higher with ultrasound guidance than with fluoroscopic guidance [ 13 ] and varies from 8.4% to 27% [ 10 , 13 ]. In our study, the malpositioning rate of the inserted cases was 18.5%, which is consistent with these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified risk factors for complications associated with the use of PICC in NBs, including gestational age (GA), catheter insertion location, catheter tip location, and catheter dwell time, especially when it is installed for greater than 35 days, a factor also associated with an increased catheter-related bloodstream infection [1,4]. Other mechanical complications appear with a lower incidence such as rupture of the catheter, migration of the catheter tip, obstruction, and leakage of drugs [5,6]. These are responsible for several non-elective removals, and many of these can be avoided as they are related to the improper handling of the device [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…Como aparato eficaz, a ultrassonografia tem trazido diversos benefícios durante o procedimento de inserção do PICC, pois contorna um dos principais desafios da técnica cega ou convencional, uma vez que auxilia a encontrar uma veia com bom diâmetro para o procedimento, minimizando os ricos para o paciente (DAWSON, 2011;KWON et al, 2020). Além da ultrassonografia, existem outras técnicas recomendadas e aplicadas por diversos profissionais, como a fluoroscopia (BOO et al, 2020;CHAN et al, 2017) e tecnologias de navegação que permitem a visualização em tempo real da localização do cateter (TOMASZEWSKI et al, 2017).…”
Section: Discussão 5 Discussãounclassified